Properties of the Binary Black Hole Merger GW150914 - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (Amer Physical Soc, 2016)
On September 14, 2015, the Laser Interferometer Gravitational-Wave Observatory (LIGO) detected a gravitational-wave transient (GW150914); we characterize the properties of the source and its parameters. The data around the time of the event were analyzed coherently across the LIGO network using a suite of accurate waveform models that describe gravitational waves from a compact binary system in general relativity. GW150914 was produced by a nearly equal mass binary black hole of masses 36(-4)(+5) M-circle dot and 29(-4)(-4) M-circle dot; for each parameter we report the median value and the range of the 90% credible interval. The dimensionless spin magnitude of the more massive black hole is bound to be < 0.7 ( at 90% probability). The luminosity distance to the source is 410(-180)(+160) Mpc, corresponding to a redshift 0.09(-0.04)(+0.03) assuming standard cosmology. The source location is constrained to an annulus section of 610 deg(2), primarily in the southern hemisphere. The binary merges into a black hole of mass 62(-4)(+4) M-circle dot and spin 0.67(-0.07)(+0.05). This black hole is significantly more massive than any other inferred from electromagnetic observations in the stellar-mass regime.